Cage-like phosphate flame-retardant micro-crosslinked polymer and preparation method thereof

Through the opening bonus reactions of the polygon oxygenic group compounds and the tetraol cage -shaped phosphate PEPPA, a CPFR CPFR of a micrococcus plymicide polymer of the cage -shaped phosphate is constructed, which solves the water resistance and solvent resistance of the existing phosphate flame retardant Insufficient problems have achieved efficient solid -state flame retardant development.

CN119350599APending Publication Date: 2025-01-24BEIJING TECH & BUSINESS UNIV

Patent Information

Application Number
CN202411292540.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing phosphate flame retardants have problems such as poor hydrolysis resistance, poor polar solvent resistance, and easy migration in polymers. The liquid phosphate is difficult to add feeding during processing, and lacks solid state with high flame retardant efficiency. New macromolecular phosphate compounds.

Method used

Through the ring-opening addition reaction of polyepoxy group compounds and pentaerythritol caged phosphate PEPA, a caged phosphate micro-cross-linked polymer CPFR is constructed to form a micro-cross-linked structure to improve water resistance and solvent resistance.

Benefits of technology

CPFR, which has excellent water resistance, solvent resistance, and high flame retardant efficiency, can maintain flame retardant performance in different environments, and is suitable for flame retardant improvement in various materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350599A_ABST
    Figure CN119350599A_ABST
Patent Text Reader

Abstract

The invention discloses a caged phosphate flame-retardant micro-crosslinked polymer and a preparation method thereof. The polymer is a halogen-free organic phosphate flame-retardant micro-crosslinked polymer solid material with water resistance and organic solvent resistance, which is prepared by addition through a ring-opening reaction of hydroxyl-containing caged phosphate and a multi-epoxy group compound under a heating condition. Through aggregation and protection of caged phosphate in a network structure in cross-linked polymer macromolecules, comprehensive improvement of flame retardance, water resistance and solvent resistance is realized, and compared with a traditional phosphorus-containing flame retardant, the flame retardant has the advantages that the flame retardance is improved; according to the flame-retardant micro-crosslinked polymer, other flame-retardant groups can be introduced through different epoxy compounds while organic phosphate groups are enriched, so that synergistic interaction of the flame-retardant groups is realized, and a flame retardant compound with more excellent performance is obtained. The polymer raw materials are easy to obtain, the preparation process is simple and convenient, and the flame retardant is good in thermal stability and comprehensive performance, can be used for flame retardant polyolefin, TPU and the like, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a halogen-free organic phosphate flame-retardant micro-crosslinked polymer and a preparation method thereof, belonging to the technical field of flame retardant synthesis and preparation, and specifically to a ring-opening addition reaction of a polyepoxy group compound and a hydroxyl-containing compound. Background Art

[0002] Organic phosphates are a class of highly efficient halogen-free and environmentally friendly flame retardants with the advantages of good compatibility with the substrate, resistance to migration, resistance to volatility, low toxicity, and relatively long-lasting flame retardant effects. At present, phosphates have developed from the first generation of triphenyl phosphate (TPP) (CN202011605709.6) to pentaerythritol caged phosphate (PEPA), triethyl phosphate (TEP), tributyl phosphate (TBP) bisphenol A bis (diphenyl) phosphate (BDP), resorcinol bis (diphenyl) phosphate (RDP) (CN202111567570.5, CN202310834673.6, CN2018104993 55.8, CN202011347829.0) and other products, while having certain flame retardant properties, also have a certain plasticizing effect on the material; however, the existing phosphate flame retardants are mostly liquid phosphates, and are small molecule flame retardants or linear single-component macromolecules, which have the disadvantages of poor hydrolysis resistance, poor polar solvent resistance and easy migration in polymers in practical applications; and the liquid phosphates also have the problem of difficulty in adding materials during the processing; therefore, at the current stage, it is very urgent to develop solid phosphate flame retardants with water resistance and organic solvent resistance, especially new macromolecular phosphate compounds with higher flame retardant efficiency.

[0003] In the research on constructing new high-efficiency macromolecular flame retardants, the aggregation and synergistic effect of different flame retardant groups is an effective means to obtain high flame retardant efficiency macromolecules; among them, the double-base macromolecular flame retardant containing phosphaphenanthrene groups (CN201910352562.5 and CN202010390988.2) is used in epoxy resins, polycarbonates, polyamides, polyurethanes and their foam materials, which can effectively improve the flame retardant properties of materials; Patent CN202111547238.2 discloses a flame retardant The halogen-free flame retardant polyolefin composite material is prepared by melt blending a halogen-free flame retardant macromolecule obtained by multi-block or random copolymerization with polyolefin. The two have good compatibility and can give the material good flame retardant properties, while significantly improving the tensile strength, elongation at break and impact strength of the material. In the above patents, there is no test on the solvent resistance and water resistance of the flame retardant material. The existing reports cannot support the durability evaluation of the above organophosphorus flame retardants under certain specific conditions of use, which limits the application and research of flame retardants in specific use environments.

[0004] Based on this, the present invention appropriately aggregates different flame retardant groups in the same macromolecule, which is not only conducive to the synergistic effect between the groups, but the micro-cross-linked structure formed by the aggregation will also increase the water resistance and solvent resistance of the macromolecule, thereby obtaining a new micro-cross-linked flame retardant with excellent comprehensive performance. Specifically, a new caged phosphate micro-cross-linked polymer flame retardant (CPFR) is constructed through the aggregation of epoxy compound structure and caged phosphate structure. The method is simple to prepare, and the obtained micro-cross-linked polymer is solid and has excellent water resistance and solvent resistance. At the same time, the synergistic effect of different flame retardant groups in the micro-cross-linked polymer flame retardant is enhanced, and the flame retardant efficiency is effectively improved. Summary of the invention

[0005] The first object of the present invention is to provide a caged phosphate flame retardant micro-crosslinked polymer, referred to as CPFR, a solid crosslinked polymer flame retardant containing a caged phosphate structure, which is one of the following compounds or a mixture of multiple thereof:

[0006] Caged phosphate compounds:

[0007]

[0008] Caged phosphate oligomers:

[0009]

[0010] Caged phosphate micro-crosslinked polymer:

[0011]

[0012] Among them, R is The continuous part in A3, B3, and C3, i.e., the wavy line, represents a repeated unit structure, and the unit structures correspond to:

[0013]

[0014] When the CPFR is the mixture, the caged phosphate micro-crosslinked polymer is the main component.

[0015] The main raw materials of the CPFR of the present invention are PEPA and polyepoxy compounds; the molecular structure of PEPA is as follows:

[0016]

[0017] The second object of the present invention is to provide a method for preparing CPFR, which involves ring-opening addition of pentaerythritol caged phosphate PEPA with a polyepoxy compound, specifically comprising: under heating conditions, or heating in the presence of a catalyst, using PEPA and a polyepoxy compound as raw materials for ring-opening addition, grafting the caged phosphate structure onto the polyepoxy compound, or continuing to allow the hydroxyl groups generated by the ring-opening addition reaction to continue to react with the epoxy groups of the polyepoxy compound, thereby obtaining a micro-crosslinked structure, and preparing a caged phosphate flame-retardant micro-crosslinked polymer with water-resistant and organic solvent-resistant properties; with the continuous growth and aggregation of the crosslinked structure, the hydrophobicity and solvent resistance of the CPFR micro-crosslink increase, and the flame retardant performance is enhanced by the aggregation of the caged phosphate in the crosslinked polymer macromolecule on the micro-crosslinked structure, thereby obtaining a solid flame retardant compound with better comprehensive performance.

[0018] Preferably, the preparation method is specifically as follows: after the polyepoxy compound and pentaerythritol caged phosphate PEPA are uniformly mixed together with an organic solvent at 20-150° C., a catalyst is added or no catalyst is added, and the mixture is kept warm for 1-48 hours, and then the solvent is evaporated under reduced pressure, and the reaction prepolymer is further heated to 60-250° C. and kept warm for 0.5-48 hours. The solid material obtained after cooling is the flame retardant CPFR.

[0019] Preferably, the polyepoxy compound is one of 2,4,6-tris(oxiran-2-ylmethoxy)-1,3,5-triazine, tris(oxiran-2-ylmethyl)benzene-1,3,5-tricarboxylate, triglycidyl isocyanurate, pentaerythritol tetraglycidyl ether, and 1,4-bis[(glycidyloxy)methyl]cyclohexane.

[0020] Preferably, the molar ratio of PEPA to the polyepoxy compound is 1.0-5.0. The composition of the obtained product varies depending on the polyepoxy compound used and the feed ratio of PEPA to the polyepoxy compound. In addition, since the hydroxyl group generated by the ring-opening addition reaction of PEPA and the polyepoxy compound in the present invention can continue to react with the epoxy group of the polyepoxy compound, the obtained product is usually a mixture. When 2,4,6-tris(oxiran-2-ylmethoxy)-1,3,5-triazine is used as the polyepoxy compound, A1, A2, and A3 are generated; when tris(oxiran-2-ylmethyl)benzene-1,3,5-tricarboxylate is used as the polyepoxy compound, B1, B2, and B3 are generated; when isocyanurate is used as the polyepoxy compound, When triglycidyl ether of acid is used as the polyepoxy compound, C1, C2 and C3 are generated; in the above three reaction processes, the main products of each are A3, B3 and C3 respectively. When the feed ratio n is less than 3, A3, B3 and C3 account for more than 95% of the products, and when 3≤n≤5, A3, B3 and C3 account for more than 70%; when pentaerythritol tetraglycidyl ether is used as the polyepoxy compound, D1 and D2 are generated, when the feed ratio n>4, the main product is D1, and when the feed ratio is 1≤n≤4, D2 is mainly generated; when 1,4-bis[(glycidyloxy)methyl]cyclohexane is used as the polyepoxy compound, E1 and E2 are generated, when n>2, the main product is E1, and when n≤2, the main product is E2.

[0021] Preferably, the added organic solvent is preferably N,N-dimethylformamide DMF, and the mass of DMF is 0 to 10 times the mass of PEPA.

[0022] Preferably, the catalyst is one or more of triethylamine, aniline, tetraethylammonium bromide, tetrabutylammonium bromide, 4-dimethylaminopyridine, and 4-(aminomethyl)pyridine, and the total molar amount of the catalyst added is 0-10% of the molar amount of the epoxy group.

[0023] The caged phosphate flame retardant micro-crosslinked polymer CPFR of the present invention adopts a ring-opening addition method, the method is simple, the selected solvent is easy to recover, and it is suitable for industrial scale-up production; and the flame retardant micro-crosslinked polymer CPFR of the present invention is a solid material, has good thermal stability, and the 1wt% thermal decomposition temperature is 240-280°C, which meets the processing requirements of general plastics and elastomers and other materials. Compared with small molecule flame retardants or flame retardant molecules polymerized from a single component, it has excellent water and solvent resistance. CPFR does not hydrolyze in a water boiling experiment and does not produce acidic substances. The micro-crosslinked structure flame retardant CPFR can show excellent flame retardant properties in TPU materials.

[0024] Beneficial effects:

[0025] The halogen-free solid flame retardant of the present invention has good flame retardant effect, and the flame retardant composite material can pass UL-94V-0 level, 1.6mm, and the flame retardant effect does not decrease after being boiled in water at 80°C for 48 hours. The preparation method of the flame retardant of the present invention has simple steps and obvious effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Infrared spectra of the CPFR and reactants obtained in Example 4;

[0027] Figure 2 Thermogravimetric curve of CPFR obtained in Example 4;

[0028] Figure 3 Example 4 Obtained CPFR and Reactants 13 C NMR spectrum;

[0029] Figure 4 HRR curves of the CPFR and PEPA flame-retardant TPU composites obtained in Example 6;

[0030] Figure 5 DSC curves of CPFR and reactants obtained in Example 4. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with examples; these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention; the experimental methods in the following examples without specifying specific conditions are generally based on conventional conditions in the art; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets; any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention are within the scope of protection claimed by the present invention.

[0032] Example 1

[0033] PEPA (21.62 g, 0.12 mol) and 2,4,6-tris(oxiran-2-ylmethoxy)-1,3,5-triazine (11.89 g, 0.04 mol) were dissolved in DMF (70 ml) at 60°C, and triethylamine (0.12 g, 0.0012 mol) and 4-(aminomethyl)pyridine (0.13 g, 0.0012 mol) were added to catalyze the reaction of PEPA and 2,4,6-tris(oxiran-2-ylmethoxy)-1,3,5-triazine for 6 h, and then The system was heated to 120°C and then distilled under reduced pressure. After 97% of DMF was distilled out, the remaining viscous liquid was transferred to a 180°C forced air oven and the reaction was continued for 3 hours. The obtained micro-cross-linked aggregates were insoluble in water and DMF, and there was no glass transition and melting point in the DSC test. By testing the gel content of CPFR (DMF was the solvent), it was found that the mass fraction of the A3 structure in the product obtained in this example was 86.9%, and the obtained product was a mixture of A1, A2, and A3, and its 1% weight loss temperature under a nitrogen atmosphere was 266.8°C.

[0034] Example 2

[0035] PEPA (64.84 g, 0.36 mol) and pentaerythritol tetraglycidyl ether (43.25 g, 0.12 mol) were dissolved in DMF (100 ml) at 90°C, and reacted for 3 h under the catalytic conditions of aniline (0.11 g, 0.0012 mol) and tetraethylammonium bromide (0.76 g, 0.0036 mol). The system was then subjected to reduced pressure distillation to distill out 95% DMF within half an hour. The remaining viscous liquid was transferred to a 140°C forced air oven and continued to react for 3 h. The obtained micro-crosslinked aggregates were insoluble in water and DMF, and no longer had a glass transition and melting point. The gel content test of CPFR (DMF as solvent) found that the mass fraction of the D2 structure in the product obtained in this example was 89.7%, and the obtained product was a mixture of D1 and D2, and its 1% weight loss temperature under a nitrogen atmosphere was 272.4°C.

[0036] Example 3

[0037] PEPA (10.81 g, 0.06 mol) and tri(epoxyethylene-2-ylmethyl)benzene-1,3,5-tricarboxylate (11.35 g, 0.03 mol) were melt blended at 100°C, reacted for 3 h under the catalytic conditions of tetrabutylammonium bromide (0.29 g, 0.0009 mol) and 4-dimethylaminopyridine (0.0005 g, 0.00045 mol), and the system was heated to 170°C and the reaction was continued for 3 h. The obtained micro-crosslinked aggregates were insoluble in water and DMF, and no longer had a glass transition and melting point. The gel content test of CPFR (DMF as solvent) found that the mass fraction of the B3 structure in the product of this embodiment was 95.5%, and the obtained product was a mixture of B1, B2, and B3, and its 1% weight loss temperature under a nitrogen atmosphere was 264.3°C.

[0038] Example 4

[0039] PEPA (26.75 g, 0.15 mol) and triglycidyl isocyanurate (TGIC, 17.84 g, 0.6 mol) were dissolved in DMF (180 ml) at 60°C, and the system was heated to 100°C and then distilled under reduced pressure. 90% of DMF was distilled out within half an hour. The remaining viscous liquid was transferred to a 140°C forced air oven and continued to react for 3 hours. The obtained micro-crosslinked aggregates were insoluble in water and DMF; its infrared Figure 1 As shown, the epoxy group in TGIC is at 760.3 cm -1 -843.3cm -1 At the place, through the epoxy ring-opening addition, there is no epoxy group in CPFR. Figure 3 By comparing the NMR of the raw materials and products, it was found that the triazinetrione ring in TGIC and the caged phosphate structure in PEPA existed in CPFR, and ether substances appeared in CPFR, indicating that CPFR was successfully synthesized; Figure 5 The obtained CPFR no longer has a glass transition and melting point. By testing the gel content of CPFR (DMF is the solvent), it is found that the mass fraction of the C3 structure in the product of this embodiment is 99.2%. The obtained product is a mixture of C1, C2, and C3, and its 1% weight loss temperature under a nitrogen atmosphere is 281.0°C. Figure 2 shown.

[0040] Example 5

[0041] PEPA (28.82 g, 0.16 mol) and 1,4-bis[(glycidyloxy)methyl]cyclohexane (23.78 g, 0.08 mol) were dissolved in DMF (120 ml) at 100 ° C, and 4-dimethylaminopyridine (0.29 g, 0.0024 mol) and 4-(aminomethyl)pyridine (0.09 g, 0.0008 mol) were added to react for 4 hours under catalytic conditions. Then the system was heated to 140 ° C and distilled under reduced pressure to distill out 80% DMF. The remaining viscous liquid was transferred to a 120 ° C forced air oven and continued to react for 3 hours. The obtained micro-crosslinked aggregates were insoluble in water and DMF, and no longer had a glass transition and melting point. The gel content test of CPFR (DMF was the solvent) found that the mass fraction of the E2 structure in the product of this embodiment was 99.8%, and the obtained product was a mixture of E1 and E2. The 1% weight loss temperature under a nitrogen atmosphere was 256.3 ° C.

[0042] Example 6

[0043] PEPA (28.82 g, 0.16 mol) and tri(epoxyethylene-2-ylmethyl)benzene-1,3,5-tricarboxylate (30.27 g, 0.08 mol) were dissolved in DMF (120 ml) at 90°C, and reacted for 3 h under the catalytic conditions of tetrabutylammonium bromide (0.58 g, 0.0018 mol) and 4-(aminomethyl)pyridine (0.19 g, 0.0018 mol). The system was then heated to 120°C and distilled under reduced pressure to distill out 90% of DMF. The remaining viscous liquid was transferred to a 180°C forced air oven and continued to react for 4 h. The resulting micro-crosslinked aggregates were insoluble in DMF and no longer had glassy The results show that the mass fraction of B3 in the product of this embodiment is 99.5%, and the obtained product is a mixture of B1, B2 and B3. The 1% weight loss temperature under nitrogen atmosphere is 278.5°C. 15% of the CPFR obtained in this embodiment is melt-blended with 85wt% of thermoplastic polyurethane elastomer to obtain a flame-retardant TPU composite material. The UL-94 flame retardant grade of the composite material is V-0. In the cone calorimeter test, the addition of CPFR flame retardant can reduce the pk-HRR of the material by 79.1% and increase the residual carbon by 15.7%, which is better than a single small molecule flame retardant, such as Figure 4 As shown in Table 1; More importantly, compared with traditional phosphorus-containing flame retardants, CPFR is insoluble in water or organic solvents, as shown in Table 2, and after CPFR and PEPA are boiled in 70℃ water for 1h, the pH value of CPFR aqueous solution is 7, and CPFR does not hydrolyze in 70℃ hot water. The pH value of PEPA aqueous solution is 3, and PEPA hydrolyzes to generate acidic substances in 70℃ hot water, as shown in Table 3.

[0044] Table 1. Flame retardant TPU formula and combustion test results

[0045]

[0046] Table 2. Comparison of solubility of CPFR and traditional phosphorus-containing flame retardants at 30°C

[0047]

[0048] Table 3. pH values ​​of CPFR and PEPA after boiling at 70℃

[0049] sample Solubility Solution pH PEPA Completely dissolved 3 CPFR Insoluble 7

Claims

1. A caged phosphate flame retardant micro-crosslinked polymer, characterized in that A solid micro-crosslinked polymer flame retardant CPFR formed by the ring-opening of a polyepoxy compound and a hydroxyl-containing caged phosphate; the CPFR is a mixture of one or more of the following compounds A1, B1, C1, D1, E1, A2, B2, C2, D2, E2, A3, B3, C3, wherein A1, B1, C1, D1, E1 are caged phosphate compounds, A2, B2, C2, D2, E2 are caged phosphate oligomers, and A3, B3, C3 are caged phosphate micro-crosslinked polymers; Among them, R is The continuous part in A3, B3, and C3, i.e., the wavy line, is a repeated unit structure, and the unit structures correspond to:

2. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 1, characterized in that: include: Pentaerythritol caged phosphate PEPA and a polyepoxy compound are used as raw materials, and a ring-opening addition reaction is carried out under heating conditions or in the presence of a catalyst to graft the caged phosphate structure onto the polyepoxy compound, or the hydroxyl groups generated by the subsequent ring-opening addition reaction continue to react with the epoxy groups of the polyepoxy compound to prepare a micro-crosslinked polymer flame retardant CPFR.

3. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 2, characterized in that: After the polyepoxy compound and pentaerythritol caged phosphate PEPA are uniformly mixed with an organic solvent at 20-150° C., a catalyst is added or no catalyst is added, and the mixture is kept warm for 1-48 hours. Subsequently, the solvent is evaporated under reduced pressure, and the prepolymer is heated to 60-250° C. and kept warm for 0.5-48 hours. The solid material obtained after cooling is the flame retardant CPFR.

4. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 2, characterized in that: The polyepoxy compound is one or more of 2,4,6-tris(oxiran-2-ylmethoxy)-1,3,5-triazine, tris(oxiran-2-ylmethyl)benzene-1,3,5-tricarboxylate, triglycidyl isocyanurate, pentaerythritol tetraglycidyl ether, and 1,4-bis[(glycidyloxy)methyl]cyclohexane.

5. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 2, characterized in that: The feed ratio of PEPA to the polyepoxy group compound, that is, the ratio of the amount of substances n, is 1.0-5.

0.

6. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 5, characterized in that: The composition of the obtained product varies depending on the different polyepoxy compounds used and the feed ratio of PEPA to the polyepoxy compounds. Specifically: When 2,4,6-tri(oxiran-2-ylmethoxy)-1,3,5-triazine is used as the polyepoxy compound, A1, A2 and A3 are generated; when tri(oxiran-2-ylmethyl)benzene-1,3,5 tricarboxylate is used as the polyepoxy compound, B1, B2 and B3 are generated; when triglycidyl isocyanurate is used as the polyepoxy compound, C1, C2 and C3 are generated; in the above three reaction processes, the main products are A3, B3 and C3 respectively, among which, when the feed ratio n is less than 3, A3, B3 and C3 account for more than 95% of the products, and when 3≤n≤5, A3, B3 and C3 account for more than 70%; When pentaerythritol tetraglycidyl ether is used as the polyepoxy compound, D1 and D2 are generated. When the feed ratio n>4, the main product is D1. When the feed ratio 1≤n≤4, D2 is mainly generated. When 1,4-bis[(glycidyloxy)methyl]cyclohexane is used as the polyepoxy compound, E1 and E2 are generated. When n>2, the main product is E1, and when n≤2, the main product is E2.

7. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 2, characterized in that: The organic solvent is N,N-dimethylformamide DMF, and the mass of DMF is 0 to 10 times that of PEPA.

8. The method for preparing the caged phosphate flame retardant slightly cross-linked polymer according to claim 2, characterized in that: The catalyst is one or more of triethylamine, aniline, tetraethylammonium bromide, tetrabutylammonium bromide, 4-dimethylaminopyridine and 4-(aminomethyl)pyridine, and the total molar addition amount of the catalyst is 0-10% of the molar amount of the epoxy group.

9. A caged phosphate flame-retardant micro-crosslinked polymer prepared by the preparation method according to any one of claims 2 to 8.

10. Use of the polymer according to claim 1 or 9 as a solid flame retardant.

Citation Information

Patent Citations

  • Multi-reaction functionality phosphaphenanthrene / siloxane double-base macromolecular flame retardant and preparation method thereof

    CN110105397A

  • High-elasticity halogen-free flame-retardant thermoplastic elastomer and preparation method thereof

    CN110527315A

  • A reactive phenanthrene / phosphite bibase flame retardant, its preparation method and application

    CN111763351B

  • Heat-resistant flame-retardant paper-plastic composite bag and preparation method thereof

    CN112480534A

  • A method for manufacturing fireproof material and its fireproof board

    CN112795090B

Cited By

  • Preparation process of weather-resistant flame-retardant sheath material and optical cable thereof

    CN119431939A